PELAKSANAAN TUGAS DAN WEWENANG KOMISI PEMILIHAN UMUM KABUPATEN BEKASI PADA PENYELENGGARAAN PEMILIHAN UMUM TAHUN 2019 BERDASARKAN UNDANG-UNDANG NOMOR 7 TAHUN 2017 TENTANG PEMILIHAN UMUM - Yulianninda Rahayu; Riswadi (Fakultas Hukum Universitas Borobudur, 2023)
The Bekasi Regency KPU is an election organizing institution in the Bekasi Regency area which has repeatedly held elections, starting with the elections in 2004, 2009, 2014 and 2019. However, there are always problems in organizing these elections. Therefore, this research will discuss the implementation of the duties and authority of the Bekasi Regency KPU as well as the obstacles in holding the 2019 elections. This research uses normative and empirical juridical research methods. From the results of the discussion in the research, it can be concluded that the implementation of the duties and authority of the Bekasi Regency KPU in holding the 2019 elections starts from the registration and verification of election participants to the taking of the oath/promise of members of the Bekasi Regency DPRD. The implementation of these duties and authorities has been running well and in accordance with the provisions of Article 18, Article 19 and Article 20 of Law Number 7 of 2017 concerning General Elections and its implementing regulations. Obstacles in carrying out these duties and authorities include: there are still many problems with the Voter Data Information System (Sidalih) application, there are still 15 political parties submitting a list of candidates for Bekasi Regency DPRD members on the last day of the candidate submission period, and the slow process of sending the recapitulation plenary minutes by PPK at the sub-district level, especially South Tambun District.